2022
DOI: 10.1002/jlb.3a0721-383r
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent stimulation of monocytes with CSF1 and polarizing cytokines reveals phenotypic and functional differences with classical polarized macrophages

Abstract: In atherosclerotic lesions, macrophages are exposed to CSFs and various microenvironmental cues, which ultimately drive their polarization state. We studied the expression of different CSFs in artery specimen and cultured vascular cells and assessed whether concurrent stimulation (CS) of monocytes with CSF1 and polarizing cytokines generated macrophages (CSM1 and CSM2) that were phenotypically and functionally different from classically polarized M1 and M2 macrophages. We also assessed the influence of acetyls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We have recently reported that concurrent stimulation of monocytes with CSF-1 and IFNγ or IL-4 results in polarized macrophages (M (IFNγ) and M (IL-4) , respectively) that differ phenotypically and functionally from classically polarized macrophages (M1 and M2) [23]. We therefore assessed to what extent LPS tolerance can be induced in such polarized macrophages and if this was affected by DMI.…”
Section: Dmi Does Not Affect Lps Tolerance In M (Ifnγ) and M (Il-4) P...mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported that concurrent stimulation of monocytes with CSF-1 and IFNγ or IL-4 results in polarized macrophages (M (IFNγ) and M (IL-4) , respectively) that differ phenotypically and functionally from classically polarized macrophages (M1 and M2) [23]. We therefore assessed to what extent LPS tolerance can be induced in such polarized macrophages and if this was affected by DMI.…”
Section: Dmi Does Not Affect Lps Tolerance In M (Ifnγ) and M (Il-4) P...mentioning
confidence: 99%
“…Human CD14 + cells were polarized to M (IFNγ) and M (IL-4) as previously described [23]. In brief, for M (IFNγ) and M (IL-4) polarization, CD14 + cells were concurrently stimulated for 6 days with 10 ng/mL of colony-stimulating factor 1 (CSF-1) and 100 ng/mL of IFN-γ or 10 ng/mL IL-4 (all from PeproTech, Hamburg, Germany, cat.no.300-25; 300-2; 200-04, respectively).…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…At present, the classification of macrophages into M1 and M2 types has been widely adopted in scientific research. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Through this extreme classification, macrophages are divided according to the functional differences of proinflammatory bactericidal and anti‐inflammatory and anti‐inflammatory prorepair. 17 , 18 , 19 While this dichotomy provided a valuable framework for understanding macrophage heterogeneity, recent advances in single‐cell technologies and systems biology approaches have revealed a spectrum of activation states that extend beyond the M1/M2 paradigm.…”
Section: Introductionmentioning
confidence: 99%